2. gt ⇔(x−12)2+(y−12)2+(z−12)2=2512 $(x-\frac{1}{2}+y-\frac{1}{2}+z -\frac{1}{2})^{2} \leq 3[(x-\frac{1}{2})^{2} +(y-\frac{1}{2})^{2}+(z-\frac{1}{2})^{2}]=\frac{25}{4}\Leftrightarrow \frac{-5}{2}\leq x+y+z-\frac{3}{2}\leq \frac{5}{2}\Rightarrow x+y+z\geq -1dấu "=" \Leftrightarrow x=y=z=\frac{-1}{3}$
2. gt \Leftrightarrow (x-\frac{1}{2})^{2} + (y-\frac{1}{2})^{2} +(z-\frac{1}{2})^{2}=\frac{25}{12} $(x-\frac{1}{2}+y-\frac{1}{2}+z -\frac{1}{2})^{2} \leq 3((x-\frac{1}{2})^{2} +(y-\frac{1}{2})^{2}+(z-\frac{1}{2})^{2})=\frac{25}{4} \Leftrightarrow \frac{-5}{2}\leq x+y+z-\frac{3}{2}\leq \frac{5}{2} \Rightarrow x+y+z\geq -1dấu "=" \Leftrightarrow x=y=z=\frac{-1}{3}$
2. gt
\Leftrightarrow (x-\frac{1}{2})^{2} + (y-\frac{1}{2})^{2} +(z-\frac{1}{2})^{2}=\frac{25}{12} $(x-\frac{1}{2}+y-\frac{1}{2}+z -\frac{1}{2})^{2} \leq 3
[(x-\frac{1}{2})^{2} +(y-\frac{1}{2})^{2}+(z-\frac{1}{2})^{2}
]=\frac{25}{4}
\Leftrightarrow \frac{-5}{2}\leq x+y+z-\frac{3}{2}\leq \frac{5}{2}
\Rightarrow x+y+z\geq -1
dấu "=" \Leftrightarrow x=y=z=\frac{-1}{3}$